Assessment of sugarcane cultivars with stable reaction to Xanthomonas albilineans under mechanical inoculation conditions - La O Hechavarría, María (2022)
Leaf scald caused by Xanthomonas albilineans in sugarcane is one of the most important diseases around the world since it causes severe losses in both agricultural and industrial yields. In Cuba, resistance to this disease is considered a major selection criterion within the breeding program. The aim of this work was to detect sugarcane cultivars with stable reaction to X. albilineans by using both additive main effects and multiplicative interaction (AMMI) and linear general models. For this, 16 cultivars planted simultaneously in 2015, 2016, and 2017 in two locations: Jovellanos (Matanzas) and Florida (Camagüey) in Cuba were mechanically inoculated with a bacterial isolate previously characterized by sequencing its DNA fragment. Disease severity was recorded in plant cane and first ratoon, and results were consistent in both analyses and revealed that L55-5 and C323-68 were the most susceptible cultivars and C1051-73 was the most resistant; however, C1051-73, C275-80, C86-12, C88-382, C89-147, My5514, and Ty86-28 were the most stable across the years and localities evaluated. Results will allow adapting the methodology for the evaluation of the reaction to leaf scald of new sugarcane cultivars.